Aggregation-induced ratiometric emission and mechanochromic luminescence in a pyrene-benzohydrazonate conjugate. (29th June 2018) - Li, Yao; Huang, Wei; Yong, Juan; Huang, Shuaidan; Li, Yujie; Liu, Yang; Wu, Dayu
Abstract : A structure tunable pyrene benzohydrazonate-based molecular platform exhibits a drastic aggregation-induced color change and a high solid-state quantum yield. Abstract : Luminogenic materials with aggregation-induced emission (AIE) have recently aroused great attention due to their potential application in many fields. However, aggregation induced ratiometric luminescence in addition to emission turn-on has been scarcely studied. Here, a structure tunable pyrene benzohydrazonate-based molecular platform exhibits a drastic aggregation-induced color change (Δ λ em, max ∼ 130 nm) and a high solid-state quantum yield (QYmax ∼ 54.5%). The exciting switch behaviour is triggered by intermolecular hydrogen-bonding through the carbohydrozone bridge, which leads to fixation of the molecular conformations. In addition, by virtue of the multiple excimer state of the pyrenyl unit, a broad range of carbohydrozone-based materials with high contrast mechanochromic luminescence have been developed. These systems represent stimuli-responsive optoelectronic switching devices leading toward multistate dynamic molecular systems in both solution and the solid state.